2009
DOI: 10.30638/eemj.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Measurement of Hazards in Estonian Enterprises

Abstract: The paper focuses on occupational hazards and the determination of risk levels. Indoor climate, lighting, noise, chemicals and dust are examined. A simple/flexible risk assessment method is provided. The results of measurements of occupational hazards in six industries (mechanical, printing, wood, plastic, clothing and water purification plants) in Estonia are presented. The overall purpose of the paper is to draw the attention to the importance of measurements of occupational hazards in industry and to act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The FRA tool was selected as an aid to conduct risk assessment in SMEs during the current research for the following reasons: previous studies (Järvis and Tint, 2009b;Tint et al, 2009) have successfully demonstrated the positive effect of risk assessment with the FRA tool in SMEs, particularly where employers appreciate the illustrative description of different hazards; the FRA tool connects health complaints with risk levels and therefore provides additional benefits for both employers and occupational health physicians such as guidelines for health surveillance frequencies.…”
Section: Flexible Risk Assessment Toolmentioning
confidence: 99%
“…The FRA tool was selected as an aid to conduct risk assessment in SMEs during the current research for the following reasons: previous studies (Järvis and Tint, 2009b;Tint et al, 2009) have successfully demonstrated the positive effect of risk assessment with the FRA tool in SMEs, particularly where employers appreciate the illustrative description of different hazards; the FRA tool connects health complaints with risk levels and therefore provides additional benefits for both employers and occupational health physicians such as guidelines for health surveillance frequencies.…”
Section: Flexible Risk Assessment Toolmentioning
confidence: 99%
“…The risk evaluation sustains SMEs in the uncertainties elimination in the development strategy and management policies (see figure 2). Estimation, evaluation and control of the occupational risk represent prerequisites for grounding and for a continual support of the decision that has been previously taken on occupational safety in a working system (Vasilescu et al, 2008;Tint et al, 2009). However, in the last time, a lot of research in the field of knowledge management is dedicated to large companies or international concerns and the small and medium-sized enterprises were forgotten.…”
Section: Introductionmentioning
confidence: 99%